2013
DOI: 10.1111/eci.12117
|View full text |Cite
|
Sign up to set email alerts
|

Pathophysiological role of the renin–angiotensin system on erectile dysfunction

Abstract: Background The renin-angiotensin system (RAS) has been shown to play an active role within the erectile tissues. The aim of this narrative review is to summarize the literature addressing the pathophysiological role of RAS on erectile function. Additionally, we update evidence on recent findings on the role of the Ang-(1-7) and Mas receptor on the erectile function and its therapeutic potential for treating erectile dysfunction (ED).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
35
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 37 publications
(36 citation statements)
references
References 89 publications
(205 reference statements)
1
35
0
Order By: Relevance
“…The renin-angiotensin system (RAS) plays an important role in the maintenance of blood pressure and tissue perfusion [16]. RAS not only functions in the cardiovascular system, including regulation of blood pressure, but also in the central nervous system [9].…”
Section: Discussionmentioning
confidence: 99%
“…The renin-angiotensin system (RAS) plays an important role in the maintenance of blood pressure and tissue perfusion [16]. RAS not only functions in the cardiovascular system, including regulation of blood pressure, but also in the central nervous system [9].…”
Section: Discussionmentioning
confidence: 99%
“…A national opinion study of 4017 participants aged 57-85 years found no consistent association between antihypertensive drug classes and sexual problems [149]. A pathophysiological role for the reninangiotensin system in ED involving angiotensin has been raised [150].…”
Section: Sexual Dysfunctionmentioning
confidence: 99%
“…The increase in the production of angiotensin-II as a result of elevated angiotensin-I converting enzyme (ACE) activity induces ED (Bader 2010;Fraga-Silva et al 2013;Oboh et al 2015;Akomolafe et al 2016). Therefore, the inhibition of ACE activity in turn reduces angiotensin-II levels and improves erectile function in ED patients (Dorrance et al 2002).…”
Section: Introductionmentioning
confidence: 99%